Er:YAG pre-treatment for bonding of orthodontic bracket: 1 year of in vitro treatment - de Jesus Tavarez RR; Lima Bezerra G; de Souza Penha KJ; Torres CRG; Firoozmand LM (Clinical, Cosmetic and Investigational Dentistry, 2017)
Rudys Rodolfo de Jesus Tavarez,1 Gisele Lima Bezerra,2 Karla Janilee de Souza Penha,3 Carlos Rocha Gomes Torres,4 Leily Macedo Firoozmand5 1Department of Dentistry, Ceuma University (UNICEUMA), 2Dentistry Program, Ceuma University (UNICEUMA), 3Dentistry Program, Federal University of Maranhão, UFMA, São Luís, MA, 4Restorative Dentistry Department, ICT UNESP University, São Paulo, 5Dentistry Department I, Federal University of Maranhão,UFMA, São Luís, MA, Brazil Objective: The aim of this study was to evaluate in vitro bond strength of metal brackets bonded with: total etch, total etch with erbium: yttrium aluminum garnet laser (Er:YAG) and self-etching adhesive systems, submitted to thermal-mechanical cycling, simulating 1 year of orthodontic treatment.Materials and methods: For the study, 80 bovine incisors were randomly divided into 3 experimental groups (n=16 each): XT- acid etching + Transbond XT, XT/Er:YAG- Transbond XT associated with Er:YAG laser irradiation (λ=2.94 μm, 60 mJ, 10 Hz) and SEP- Transbond Plus Self Etching Primer. Samples were submitted to thermal-mechanical cycling, simulating 1 year of orthodontic treatment. Afterward, the shear bond strength test was performed in a universal test machine at a speed of 0.5mm/min. Samples were evaluated under a stereomicroscope and by scanning electron microscopy for analysis of enamel surface and adhesive remnant index. Data were analyzed using Kruskal–Wallis and Mann–Whitney (with Bonferroni correction) statistical tests.Results: Statistically significant difference was observed between the groups studied (p<0.05). Groups XT and SEP showed the highest bond strength values, without statistical difference between them, while group XT/Er:YAG showed reduction in bond strength values. Higher frequency of adhesive failures between enamel and adhesive system was verified for groups XT and XT/Er:YAG.Conclusion: The conventional (XT) and self-etching (SEP) adhesive systems showed mean bond strength values, similar between them, whereas the previous application of Er:YAG laser promoted the lowest bond strength values. Keywords: dentin-bonding agents, orthodontic brackets, shear strength, enamel, YAG laser, self-etching adhesive system, orthodontic bonding